Effect of labor and number of micro and small enterprises (MSEs) on poverty rate in Indonesia - Siti Hodijah; Candra Mustika (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
The study aims to analyze the poverty and micro and small enterprises in 34 provinces in Indonesia, and to analyze the effect of labor and the number of micro and small enterprises on poverty levels in Indonesia. The results indicate that Papua Province has the highest poverty rate and the DKI Jakarta Province has the lowest poverty rate. Central Java Province has the largest number of micro-enterprises, and West Papua Province has the lowest number of micro-enterprises. For small enterprises, Central Java Province has the highest number and West Papua Province has the lowest number. Meanwhile, Central Java Province as the largest number of micro-business workers, and West Papua Province has the lowest number workers. For small business workers, Central Java Province has the largest number and West Papua Province has the lowest number. The results of panel data regression show that some variables, such as small-enterprise worker and the number of micro enterprises, have a significantly negative effect on the poverty rate. On the other hand, micro-enterprise worker and the number of small enterprises have a positive and significant effect on poverty rate.